The effect of behavioral therapy based counseling with anxious mothers on their infants' colic: a randomized controlled clinical trial - Reihaneh Montazeri; Shirin Hasanpour; Mojgan. Mirghafourvand; Manizheh Mostafa Gharehbaghi; Mohammad Mehdi Ghods Tehrani; Shiva Mohajjel Rezaei (BMC, 2022)
Abstract Background Given the possible effect of maternal anxiety on the severity of colic pain in infants, this study aimed to investigate the effects of behavioral therapy counseling on infantile colic (primary outcome), maternal anxiety, and mother-infant attachment (secondary outcomes) in anxious mothers with colicky infants. Method This randomized controlled clinical trial was conducted on 46 anxious mothers of 2-6-weeks-old exclusively breastfed colicky infants who had a score of 112 and above according to the Postpartum Specific Anxiety Scale (PSAS), reffered to the pediatric clinics of Al-Zahra, Taleghani and Children Hospitals of Tabriz, Iran. The participants were randomly assigned to the intervention (n = 23) and control (n = 23) groups using randomized block design. Mothers in the intervention group attended 8 systematic desensitization counseling sessions (2-3 sessions per week). Those in the control group received routine care. The researcher completed the Postpartum Specific Anxiety Scale (PSAS), Mother-Infant Attachment Questionnaire (MIAQ), and Infant Colic Scale (ICS) by interviewing the participants before and two weeks after the intervention. Results There was no significant difference between the intervention and control groups in the socio-demographic profile of participants. After the intervention, the mean postpartum anxiety score of women in the intervention group was significantly lower than that of those in the control group (Mean Difference (MD) = 22.5, 95% Confidence Interval (CI) = 2.3 to 42.7; p = 0.029). The mean infant colic score of the infants of mothers in the intervention group was insignificantly lower than that of those in the control group (MD = -2.9, 95% CI = -8.3 to 2.4; p = 0.271). In addition, no significant difference was observed between the two groups in terms of their mean mother-infant attachment scores (MD = -0.04, 95% CI = -3.1 to 0.3; p = 0.976). Conclusion Behavioral therapy counseling effectively reduced postpartum anxiety in women with colicky infants; however, this reduction did not lead to a significant decrease in the infants' colic pain. Therefore, health care providers are recommended to use this counseling method in combination with other effective counseling approaches to promote mental health of these mothers. Trial Registration IRCT Registration Number: IRCT20111219008459N14, registered on 08/10/2020. https://irct.ir/user/trial/45949/view